Combination of tuna fish and green spinach on the quality of nuggets - Faizah Hamzah; Bella Vista; Rahmayuni Rahmayuni; Angga Pramana (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Tuna is an adequate source of animal protein tall. Animal-based food ingredients such as tuna have high protein content but low in fiber so it is necessary to add materials that contain fiber to meet the nutrients the body needs. Fiber that is contained in plant materials such as vegetables and nuts, one of which is found in green spinach. Nutritional content in green spinach which is quite high and the availability of many ingredients, provide opportunities to be utilized in processing diversification foods such as nuggets. Nuggets are processed products made from ground meat mixture and may or may not contain other ingredients or approved food additives. Nuggets in this study were made from cobs and green spinach. The study aims to get the best formulations of cobs nuggets and green spinach that meet the best sensory and chemical properties. The study's design is a Complete Randomized Design (RAL) with five treatments and three repeats. The data was statistically analyzed using variance analysis (ANOVA) and Duncan's test (DMRT) at a level of 5%. Treatment consists of TB1 (cob and spinach [90:10]), TB2 (cob and spinach [80:20]), TB3 (cob and spinach [70:30]), TB4 (cob and spinach [60:40]), and TB5 (cob and green spinach [50:50]). In this study, the combination of cobs and spinach affected water content, ash content, fibre and protein, and the sensory assessment of nuggets in terms of colour, aroma, taste, and texture. The best treatment is TB2 (cobs and green spinach [80:20]) with a moisture content of 56.82%, ash content of 1.44%, protein content of 13.74% and fibre content of 2.45%, with preferred TB2. Panellists rated the nuggets as greenish-grey, highly flavorful cobs, flavoured cobs and chewy textures